Cultural and creative industries in the fourth industrial revolution: heterodox economic perspectives on the EU’S triple transition - Valiati, Leandro; Möller, Gustavo (Frontiers in Communication, 2025)
This paper examines the transformative impact of the Fourth Industrial Revolution (4IR) on Cultural and Creative Industries (CCIs) and their role in advancing the European Union’s triple transition—green, digital, and social. It explores how technological disruption interacts with structural inequalities, institutional frameworks, and human capabilities, drawing on heterodox economic perspectives to provide a comprehensive analysis. The study adopts a qualitative and exploratory approach, combining theoretical synthesis with sectoral evidence from European CCIs. The findings indicate that while 4IR technologies offer unprecedented opportunities for creative expression, global reach, and new forms of collaboration, they also reinforce digital dependency, structural heterogeneity, and capability trade-offs. Concentrated platform power, algorithmic gatekeeping, and data extraction reproduce historical centre–periphery dynamics, while productivity gaps between high-tech and traditional creative sectors deepen social inequalities. At the same time, digital tools expand access to resources and audiences, opening new avenues for participation and innovation. The analysis suggests that technological progress alone cannot secure inclusive development; instead, institutional reform, capability enhancement, and alternative economic models are essential to align CCIs with Europe’s wider social and environmental objectives. By synthesising insights from structuralist economics, dependency theory, capability approaches, and institutional analysis, the paper develops an integrated model for understanding CCIs as both vulnerable and as drivers of transformative change. The results provide policy guidance on promoting creative autonomy, technological sovereignty, and cultural diversity within the EU’s triple transition.